Implementation of Distance Learning in Ukraine - Kolbina, Tetiana; Oleksenko, Olena (Educational Challenges, 2020)
The pandemic has put the higher education of Ukraine to new challenges. The objectives of the article are to describe the implementation of distance learning in Ukraine, illustrate the personal learning systems and their levels, provide practical examples of the content of personal learning systems. The theoretical and methodological base of the research of distance learning consists of an activity approach that is grounded on the psychological theory of activity and the concept of personally oriented learning, directed at the formation and development of students’ subjectivity, with due regard to their individual abilities. Results are the following. Studying during the lockdown has essentially speeded the implementation of various forms and technologies of distance education, actualized the tasks to modernize its organization, search for efficient methods of managing the process of studying, has provoked the necessity for teachers to improve their level of mastering information and communication technologies. The concept of development of distance education in Ukraine has emphasized that it creates conditions for the realization of the system of continuous “life-long learning” and provides individualization of studying by mass education. Meanwhile, this organization should be built as a pedagogical system that consists of the elements (goals, principles, content, methods, and forms of the educational activity) and is realized by information and communication technologies. In S. Kuznets Kharkiv National University of Economics distance learning is supported by PNS (personal learning systems) that consist of content, interactive and autonomous levels. The content of the given levels is characterized and supported by practical examples. Conclusion: implementation of distance learning in such a form enables the renewal of content, forms and methods of studies according to current demands of the society in innovative development; individualization of the educational process with due regard to demands of those who study as well as optimization of the whole educational process.